Respons Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) Terhadap Decanter Solid dan Pupuk Phospor di Pembibitan Utama - Sarman Sarman; Elly Indraswari; Ahmad Husni (Universitas Batanghari, 2021)
Oil palm is one of the most important plantation crops in the plantation sector in Indonesia. Oil palm (Elaeis guineensis Jacq) is a vegetable oil-producing plant in the form of Crude Palm Oil (CPO). CPO productivity is very much determined by quality and productive seeds. Oil palm (Elaeis guineenses Jacq) is a vegetable oil-producing plant which produce Crude Palm Oil (CPO). This study aims to determine the response of oil palm seedling growth to the provision of solid food containers and phosphate fertilizers at various doses in the main nursery. This research was conducted at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, Mendalo Indah, Jambi Luar Kota District, Muaro Jambi Regency. This research was conducted for 3 months from September to December 2019. Design of the experiment used a randomized block design (RBD) with one factor, the application of various solid decanter compositions consisting of 6 treatments levels : p0= fertilizer NPKMg 44g/polybag; p1=decanter solid 140 g + 13 g (TSP) / polybag; p2=decanter solid 240 g + 13 g (TSP) / polybag; p3 = decanter solid 340 g + 13 g (TSP)/polybag; p4 = decanter solid 440 g + 13 g (TSP)/polybag; and p5 = decanter solid 540 g + 13 g (TSP) / polybag. Variables observed were plant height, number of leaves, stem diameter, total leaf area, root dry weight, shoot dry weight, and root shoot ratio. The results showed that giving solid decanter at various doses was able to increase growth in all observed variables and was able to sow seedling growth at recommended fertilization doses. The application of solid decanter 140 g + 13 g (TSP) is the best dose to increase the seed height variable and able to exceed the seed height at the recommended dose of fertilizing oil palm seedlings in the main nursery.